2000
DOI: 10.1079/095442200108728990
|View full text |Cite
|
Sign up to set email alerts
|

Value of traditional foods in meeting macro- and micronutrient needs: the wild plant connection

Abstract: The importance of edible wild plants may be traced to antiquity but systematic studies are recent. Anthropologists, botanists, ecologists, food scientists, geographers, nutritionists, physicians and sociologists have investigated cultural aspects and nutrient composition of edible species. Important contributions to the diet from edible wild plants are well documented and numerous studies reveal roles played by`lesser-known' species when meeting macro-and micronutrient needs of groups at risk, whether infants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
238
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 322 publications
(260 citation statements)
references
References 79 publications
4
238
0
1
Order By: Relevance
“…Grivetti and Ogle (2000) observed that edible wild plants were regular components of the diets of millions of people. Despite the fact that in more recent times human diets have used relatively few plant species, which also encompasses the decline of plant use knowledge, subglobal assessments show that several indigenous and traditional communities currently consume 200 or more species (Grivetti & Ogle 2000;MEA 2005).…”
Section: Contribution Of Wild Edible Plants To People's Diets and Daimentioning
confidence: 99%
See 2 more Smart Citations
“…Grivetti and Ogle (2000) observed that edible wild plants were regular components of the diets of millions of people. Despite the fact that in more recent times human diets have used relatively few plant species, which also encompasses the decline of plant use knowledge, subglobal assessments show that several indigenous and traditional communities currently consume 200 or more species (Grivetti & Ogle 2000;MEA 2005).…”
Section: Contribution Of Wild Edible Plants To People's Diets and Daimentioning
confidence: 99%
“…Lack of knowledge and inability to identify plants existing in the wild and available to sustain survival have led to malnutrition and hunger in certain areas of the world (Grivetti & Ogle 2000).…”
Section: Famine Foodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wild foods can be obtained from forests and other areas of natural diversity or from agricultural land or around the home (Bharucha & Pretty 2010). The consumption of wild foods appears to be common across the world (Scoones et al 1992;Grivetti & Ogle 2000;Bharucha & Pretty 2010) and in certain contexts may provide a significant proportion of fruits, vegetables and animal source foods .…”
Section: Introductionmentioning
confidence: 99%
“…Human body cannot produce ascorbic acid, so it must be obtained entirely through ones diets. The protective action of fruits and vegetables has been attributed to the presence of anti-oxidants, especially anti-oxidant vitamins including ascorbic acid and beta-carotene [28,29]. Considering the pivotal roles of this water soluble vitamin in human health, minimal infusion time (5 min) should be employed for H. crinita leaf in order to minimize its loss.…”
Section: Effect Of Treatment On Vitaminsmentioning
confidence: 99%